Effects of extended Zilpaterol-HCl withdrawal on performance and carcass traits of finishing beef heifers - G.L. Parsons; Brandon E. Depenbusch; Christopher D. Reinhardt; D.A. Yates; J.P. Hutcheson; James S. Drouillard (Kansas Agricultural Experiment Station Research Reports, 2010)
Zilpaterol-HCl (Zilmax; Intervet/Schering-Plough Animal Health, Millsboro; DE) is an orally active β2-adrenergic agonist that is approved for use in feedlot cattle at the rate of 7.56 g/ton of diet dry matter for the final 20 to 40 days on feed. The minimum withdrawal time for Zilmax is 3 days. Zilmax increases hot carcass weight and dressing percentage, primarily as a result of increasing lean muscle mass and decreasing body fat. Zilmax also decreases marbling and increases shear-force values (i.e., less tender) of steaks. This study was conducted to determine whether the benefits of Zilmax would be retained with longer withdrawal times while overcoming undesirable effects on shear force and marbling.
Keywords: Cattlemen' s Day; 2010; Kansas Agricultural Experiment Station contribution; no. 10-170-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 1029; Beef Cattle Research; 2010 is known as Cattlemen' s Day; Beef; Zilpaterol-HCl; Performance; Carcass traits; Heifers